Unraveling New Binding Partners of Atg3 in Autophagy and Mitophagy - Oz\\-Arslan, D.; Acikgoz, D.; Kan, B.; Durer, Z. A. (SPRINGER, 2019)
Joint 12th EBSA European Biophysics Congress / 10th IUPAP International Conference on Biological Physics (ICBP), Madrid, SPAIN, JUL 20-24, 2019